2009
DOI: 10.1007/s11242-009-9412-3
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Generating Pore-Network Models of Porous Media

Abstract: In this study, we have developed a new method to generate a multi-directional pore network for representing a porous medium. The method is based on a regular cubic lattice network, which has two elements: pore bodies located at the regular lattice points and pore throats connecting the pore bodies. One of the main features of our network is that pore throats can be oriented in 13 different directions, allowing a maximum coordination number of 26 that is possible in a regular lattice in 3D space. The coordinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
116
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 158 publications
(118 citation statements)
references
References 47 publications
0
116
1
1
Order By: Relevance
“…For example, Øren and coworkers [Øren et al, 1997;Øren et al, 1998;Bakke, 2002, 2003] developed pore-network models of real sandstones and reported mean coordination numbers of 3:5 À 4:5. In the present study, we employ an MDPN model in which pore throats can be oriented in 13 different directions, allowing a maximum coordination number of 26 [Nogues et al, 2012;Vasilyev et al, 2012;Raoof and Hassanizadeh, 2009]. To get a desired coordination number distribution, we follow an elimination procedure to rule out some of the connections (for details, see Raoof and Hassanizadeh [2009]).…”
Section: Coordination Number Distribution In Mdpnmentioning
confidence: 99%
“…For example, Øren and coworkers [Øren et al, 1997;Øren et al, 1998;Bakke, 2002, 2003] developed pore-network models of real sandstones and reported mean coordination numbers of 3:5 À 4:5. In the present study, we employ an MDPN model in which pore throats can be oriented in 13 different directions, allowing a maximum coordination number of 26 [Nogues et al, 2012;Vasilyev et al, 2012;Raoof and Hassanizadeh, 2009]. To get a desired coordination number distribution, we follow an elimination procedure to rule out some of the connections (for details, see Raoof and Hassanizadeh [2009]).…”
Section: Coordination Number Distribution In Mdpnmentioning
confidence: 99%
“…Pore-network models [8][9][10][11][12][13][14][15][16] are a viable tool for understanding multiphase flows at the pore scale, and they are computationally efficient. These models, however, are based upon simplified representations of the complex pore geometry [17], which restricts their predictive capability and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Xiong et al [64], there exist a number of techniques to construct a pore network model (PNM) representing a given porous medium. They may be categorized into three methods, namely, statistical reconstruction (Adler and Thovert [65], Levitz [66], Roberts and Torquato [67], Ioannidis and Chatzis [68], and Manwart et al [69]), grain-based model (Bryant et al [70], Bakke and Oren [71], Lerdahl et al [72], and Oren and Bakke [73]), and direct mapping model (Al-Raoush and Wilson [74], Jiang et al [75], Shin et al [76], and Raoof and Hassanizadeh [77]). Once the pore network structure has been established, different interesting phenomena can be investigated.…”
Section: Pore Network Modelsmentioning
confidence: 99%